Pengaruh Penggunaan Limbah Ampas Tebu Merah Sebagai Pengganti Semen terhadap Kuat Tekan Beton - Muhammad Rahman Rambe; Rizky Febriani Pohan; Alvi Sahrin Nasution; Wirna Arifitriana (Yayasan Literasi Sains Indonesia, 2024)
The aim of this research is to determine the effect of red sugar cane bagasse waste as a cement substitute on the compressive strength of concrete and to determine the compressive strength value of concrete after adding red sugar bagasse waste as a cement substitute. This research is experimental research which begins with preparation of tools and materials, aggregate inspection, slump test, job mix design, making test objects, caring for test objects, testing concrete volume weight and ends with testing concrete compressive strength. The research results show that the addition of red sugar cane bagasse powder as a cement substitute in making concrete has an effect on the mechanical properties of concrete such as: slump value, concrete volume weight and concrete compressive strength. The average compressive strength value of concrete produced after adding 2.5% red sugar cane bagasse waste; 5%; 7.5% and 10% at 28 days are 20.95 MPa respectively; 17.15 MPa; 14.79 MPa and 11.87 MPa. Thus, red sugar bagasse waste is not recommended to be used as a cement substitute because the compressive strength value of the planned concrete is very far from normal concrete.